2018
DOI: 10.3390/jcm7100351
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Two-Step Screening Strategy for Gestational Diabetes Mellitus Based on the 2013 WHO Criteria by Combining the Glucose Challenge Test and Clinical Risk Factors

Abstract: This study determines if a modified two-step screening strategy with a glucose challenge test (GCT) ≥ 7.2 mmol/L and clinical risk factors improves the diagnostic accuracy for gestational diabetes mellitus (GDM), based on 2013 WHO criteria, while limiting the number of oral glucose tolerance tests (OGTT). This was a prospective multicentric cohort study with 1811 participants receiving both GCT and 75 g OGTT in pregnancy. Participants and health care providers were blinded for GCT. Characteristics were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…In a study by Katrien Benhalima et al, the modified 2 step screening strategy with GCT and clinical risk factors improved the diagnostic accuracy. 10,11 As proved by earlier studies, in our study also the prevalence of GDM is 8.1% and majority of GDM patients were of age group 26-30 yrs. 58.3% of GDM cases were multi gravidae.…”
Section: Discussionsupporting
confidence: 79%
“…In a study by Katrien Benhalima et al, the modified 2 step screening strategy with GCT and clinical risk factors improved the diagnostic accuracy. 10,11 As proved by earlier studies, in our study also the prevalence of GDM is 8.1% and majority of GDM patients were of age group 26-30 yrs. 58.3% of GDM cases were multi gravidae.…”
Section: Discussionsupporting
confidence: 79%
“…The Belgian Diabetes in Pregnancy Study (BEDIP-N) was a multicentre prospective cohort study that has previously been described in detail [6][7][8]. The study protocol was approved by the institutional review boards of all participating centres.…”
Section: Methodsmentioning
confidence: 99%
“…Of all the BEDIP-N participants, 1813 (90.3%) received both a GCT and an OGTT between 24 and 28 weeks of pregnancy, with 228 women diagnosed with GDM (prevalence of 12.4%). Overall, 106 participants (5.3%) discontinued the study before 24 weeks of pregnancy, half because of a medical reason [8]. We have recently shown that the threshold of the GCT would need to be reduced to at least 7.2 mmol/l to achieve sensitivity of ≥70% for GDM based on the 2013 WHO criteria [7].…”
Section: Methodsmentioning
confidence: 99%
“…The Belgian Diabetes in Pregnancy study (BEDIP-N) was a multi-centric prospective cohort study that has previously been described in detail [13,14,15]. Women between 18–45 years with singleton pregnancies, and without history of diabetes or bariatric surgery, were recruited between 6–14 weeks of pregnancy [13].…”
Section: Methodsmentioning
confidence: 99%